ANALISIS PENGARUH KETEBALAN LAPISAN TERHADAP KEKASARAN PERMUKAAN PRODUK CETAK PLA MENGGUNAKAN TEKNOLOGI FDM UNTUK INDUSTRI MANUFAKTUR - Nurhidayanti; Lukmanul Hakim Arma; Rusdi Nur (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Additive manufacturing (AM), commonly known as 3D printing, uses various methods, including Fused Deposition Modeling (FDM). This study focuses on the surface roughness performance of 3D-printed propellers using FDM with PLA material. This study aims to determine the optimal layer thickness to achieve the best surface quality in additive manufacturing. Surface roughness was measured using the arithmetic mean (Ra) and measured at the propeller's centre, base, and endpoints with an Olympus laser scanning microscope. Experiments were conducted with layer thicknesses of 0.1 mm, 0.2 mm, and 0.3 mm, while keeping other printing parameters constant, namely printing temperature at 210°C, printing speed at 50%, nozzle diameter at 0.4 mm, bed temperature at 70°C, infill pattern lines, infill density at 100%, edge support type, wall thickness at 0.8 mm, and eSUN material diameter at 1.75 mm. The results show that a layer thickness of 0.1 mm produces the highest surface quality and dimensional accuracy at all tested points on the propeller, but affects the printing time. These results underline the important role of layer thickness in optimizing the surface finish and structural integrity of 3D printed components in additive manufacturing processes